1991
DOI: 10.1515/jpme.1991.19.3.185
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maternal oxygen administration on fetal and maternal blood flow values using Doppler ultrasonography

Abstract: Thirty-one pregnant women divided into three groups (AGA prepartum, SGA prepartum without distress, AGA in labor) were examined using Doppler ultrasonography before, during and after oxygen administration to mothers via a face mask. The aim of the study was to find out if there was any effect on the blood flow values in the fetal aorta, the umbilical artery, the fetal common carotid artery and the uterine arcuate arteries. The resistance index (RI) did not change in those vessels during maternal hyperoxygenati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Many studies on IUGR fetuses have reported an unchanged UA-PI following MO [29,30,38,39]. This absence of a placental response may be due to dysfunctional placental oxygen transport in IUGR fetuses, which has been shown by MRI.…”
Section: Iugr/fgrmentioning
confidence: 87%
See 2 more Smart Citations
“…Many studies on IUGR fetuses have reported an unchanged UA-PI following MO [29,30,38,39]. This absence of a placental response may be due to dysfunctional placental oxygen transport in IUGR fetuses, which has been shown by MRI.…”
Section: Iugr/fgrmentioning
confidence: 87%
“…In healthy fetuses, umbilical cord hemodynamic Doppler parameters, such as UA-PI, UA systolic and diastolic velocity, and UV blood flow, remain unchanged during MO at various levels of O 2 supplementation [28][29][30]. However, MRI has revealed that both BOLD signals and R1 of the placenta increase significantly after high-flow oxygen inhalation (12-15 L/minute), even in the short term [21][22][23].…”
Section: Fetal Hemodynamic Response In Normal Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…A lack of pulmonary vasoreactivity was shown to be poorly prognostic, predictive of fatal lung hypoplasia in conditions of potential lung under development. Investigators have used maternal hyperoxygenation to study intrauterine growth restriction, congenital diaphragmatic hernia, fetal lung hypoplasia and maternal pre‐eclampsia. Improvements in fetal circulatory Doppler flow patterns were demonstrated in growth‐restricted fetuses that received maternal hyperoxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…The observation of fetal AAS with a small, thin, underfilled LV, ultimately manifesting as a completely normal LV after birth, has led us to investigate the possibility of recreating this phenomenon before birth. Maternal hyperoxygenation in the third trimester of pregnancy has been applied in a number of conditions, both from a diagnostic and therapeutic perspective. It can promote fetal pulmonary vasodilation, thereby influencing the quantity of pulmonary venous return to the left side of the heart.…”
Section: Introductionmentioning
confidence: 99%